Distributional impact of tax and welfare policies: Budget 2026 - Bercholz, Maxime; Doorley, Karina; Keane, Claire; Mowlds, Cian; O'Shea, Richard; Simon, Agathe (ESRI, 2025)
In this Special Article we analyse the distributional impact of Budget 2026. In 2026, average household income is estimated to be 1.3% lower than it would be under a tax–welfare system indexed to price growth, and 1.9% lower than it would be under a system indexed to anticipated wage growth. While increases to welfare rates ahead of price inflation had a positive impact on lower income families, these were offset by the withdrawal of temporary cost-of-living supports, resulting in a loss overall. Middle- and higher-income households were negatively affected by the freezing of income tax credits and bands, as well as the withdrawal of these temporary cost-of-living supports. Overall losses are relatively flat across income groups and family types but are slightly larger for the lowest income 10% compared to the highest 10%. Examining the tax–welfare changes between 2020 and 2026, an interesting pattern emerges. Compared to a 2025 tax–welfare system indexed in line with either price or wage growth over this time period, households, on average, experienced a slight reduction in disposable income due to tax–welfare policy changes since 2020, with middle- and higher-income groups seeing small losses. However, the lowest income decile saw income gains compared to price or wage growth, due partly to welfare for children increasing about three times faster than prices or wages.